Special weekends of ECoC Wrocław 2016. A summary report. - Kajdanek, Katarzyna; Banaszak, Ewa; Błaszczyk, Mateusz; Pluta, Jacek (Instytut Socjologii Uniwersytet Wrocławski)
The report contains analysis of data related to special events of EcoC Wrocław 2016. They were twelve events which organized the all-year rhythm of EcoC in Wrocław. In the report the emphasis was put on the social characteristics of the participants, on the social character of their engagement and on the assessment of the events in which a lot of attention was given to a multi-sensual experience of the events. An important aspect of the research was also the analysis of qualitative data collected in an open question in the survey.
Keywords: ECoC special weekends; multi-sensual experience of events; special events